Assessing public transportation accessibility for rural communities: the case of Kampung Jeram, Pasir Puteh, Kelantan - Nasarudin, Na’asah; Raja Othman, Raja Norashekin; Abdullah, Yusfida Ayu; Marzukhi, Marlyana Azzyati; Jamaluddin, Baizura; Che Abdullah, Ishak (UiTM Press, 2025)
Public transportation is vital for urban areas, efficiently moving commuters and providing economical access to services. However, rural areas often struggle with limited public transportation, primarily along major roads far from communities, leading to transportation disadvantages for rural residents. This study evaluates public transportation accessibility for Kampung Jeram residents in accessing workplaces, commercial centers, healthcare, and education. A survey of one hundred seventy-eight (178) rural residents assessed their ability to reach key services in the town center. Findings show that Kampung Jeram's settlements are distant from essential facilities, such as schools, clinics, and shopping areas. The absence of bus services exacerbates travel challenges, particularly for students, the elderly, and those without private vehicles. These results underscore the need for local governments to adopt strategic measures to enhance rural public transportation accessibility. This study aims to support improved planning and management of public transportation in rural areas like Kampung Jeram.